Dysregulation of T cell immunoglobulin and mucin domain 3 (TIM-3) signaling in peripheral immune cells is associated with immune dysfunction in autistic children. (February 2019) - Ahmad, Sheikh F.; Ansari, Mushtaq A.; Nadeem, Ahmed; Bakheet, Saleh A.; AL-Ayadhi, Laila Y.; Alotaibi, Moureq R.; Alhoshani, Ali R.; Alshammari, Musaad A.; Attia, Sabry M.
Highlights: TIM-3 was highly expressed in cells of children with ASD. Inflammatory cytokine production in TIM-3 cells was upregulated. Foxp3 production in TIM-3 cells was decreased in children with ASD. TIM-3 signaling could be crucial for neuroimmune dysfunction in ASD children. Abstract: Evidence suggests that immune dysregulation is associated with autism spectrum disorder (ASD). T cell immunoglobulin and mucin domain-3 (TIM-3) has a critical role in several inflammatory disorders; however, the role of TIM-3 signaling has not been demonstrated in ASD. In the present study, we assessed the role of TIM-3 signaling in children with ASD. We expected that increased numbers of TIM-3 + cells could alter immune function in children with ASD. We revealed production of TIM-3 on CD3 +, CD4 +, CD8 +, CD11a +, b +, CD14 +, CD62P +, and CXCR5 + PBMCs in children with ASD and typically developing (TD) controls using immunofluorescent staining. We further demonstrated the production of IL-1β, IFN-γ, IL-17 A, and Foxp3 in TIM-3 + PBMCs of TD controls and individuals with ASD. We also observed the mRNA expression levels of TIM-3, CD11a, b, CD14, IL-1β and IFN-γ using RT-PCR. We further assessed the protein levels of TIM-3, IL-1β, CXCR5, and IFN-γ using western blotting. The results showed that children with ASD had increased numbers of CD3 + TIM-3 +, CD4 + TIM-3 +, CD8 + TIM-3 +, CD11a, b + TIM-3 +, CD14 + TIM-3 +, CD62P + TIM-3 + and CXCR5 + TIM-3 + cells compared with TD controls. Our results further showed that children with ASD had increased IL-1β + TIM-3 +, IFN-γ + TIM-3 +, and IL-17 + TIM-3 +, and decreased Foxp3 + TIM-3 + production compared with that in TD controls. Our results indicated that children with ASD significantly induced TIM-3, CD11a, b, CD14, CXCR5, IL-1β and IFN-γ mRNA and protein expression levels compared with TD controls. The results suggested that detection of TIM-3 signaling could contribute to the early diagnoses of ASD.